2017
DOI: 10.1039/c7cp06618j
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of three-domain antifreeze proteins on ice: a study using LGMMAS theory and Monte Carlo simulations

Abstract: In the present work, the adsorption of three-domain antifreeze proteins on ice is studied by combining a statistical thermodynamics based theory and Monte Carlo simulations. The three-domain protein is modeled by a trimer, and the ice surface is represented by a lattice of adsorption sites. The statistical theory, obtained from the exact partition function of non-interacting trimers adsorbed in one dimension and its extension to two dimensions, includes the configuration of the molecule in the adsorbed state, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The study in Refs. [22][23][24] confirmed also the importance of the size and structure of the protein in determining its activity. These findings are consistent with previous results addressing the effect of impurities on the growth of crystals from aqueous solutions [25].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The study in Refs. [22][23][24] confirmed also the importance of the size and structure of the protein in determining its activity. These findings are consistent with previous results addressing the effect of impurities on the growth of crystals from aqueous solutions [25].…”
Section: Introductionmentioning
confidence: 69%
“…A similar effect was reported by DeLuca et al [13], who reported that an increment in the AFP activity is observed when the type III AFP is linked to other proteins and thus its size is increased. From a theoretical point of view, several models have been proposed relating thermal hysteresis activity with the portion of ice surface occupied by AFPs [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. These approaches stimulate the researchers to develop more refined theoretical solutions for the adsorption thermodynamics of complex adsorbates (in this case, proteins of different sizes and shapes).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further comprehensive analysis of other interest systems through the proposed formalism appears necessary to discern its applicability, reliability, and accuracy. Along this line, future efforts will be devoted to the study of crystal growth in the presence of n -domains antifreeze proteins. Previous investigations in these systems point out that the structure of the adsorbate and the geometry of the lattice play essential roles in determining the thermodynamic properties of the adsorbed proteins.…”
Section: Resultsmentioning
confidence: 99%